Pelatihan Pengelolaan Keuangan Bagi Remaja - Kusuma Bakti Irianti; Dwita Sagita Ningrum; Tasya Putri Eka Sakti; Anisa Hapsari (Yayasan Kajian Riset dan Pengembangan RADISI, 2021)
Financial management socialization is carried out as a form of concern and service to the community. There are three stages of the activity method used. The first stage is a field survey by looking at the conditions and problems faced by teenagers. The second stage, the division of tasks to the Dukuh Janten Real Work Lecture (KKN) team RT 001/RW 002 by determining the topic of discussion and determining the implementation schedule. The last stage is the implementation of socialization. This socialization was carried out with the aim of providing education on how to do financial management properly and correctly, as well as providing some real examples that can be applied by teenagers. The result of this activity is that adolescent participants can understand more about the benefits of financial management and increase awareness of managing finances.